Picasso the man and his work - Quinn, Edward (New York VIEW Video, 1986)
Documents Pablo Picasso's life, with emphasis on his work throughout various periods and sources of art.
v.1. 1881-1933 -- v.2. 1938-1973.
Keywords: Picasso, Pablo; Art studies; Humanities; Fine arts